Obesity-Related Perivascular Adipose Tissue Damage Is Reversed by Sustained Weight Loss in the Rat. Issue 7 (July 2016) - Bussey, Charlotte E.; Withers, Sarah B.; Aldous, Robert G.; Edwards, Gillian; Heagerty, Anthony M.
Abstract : Objective—: Perivascular adipose tissue (PVAT) exerts an anticontractile effect in response to various vasoconstrictor agonists, and this is lost in obesity. A recent study reported that bariatric surgery reverses the damaging effects of obesity on PVAT function. However, PVAT function has not been characterized after weight loss induced by caloric restriction, which is often the first line treatment for obesity. Approach and Results—: Contractility studies were performed using wire myography on small mesenteric arteries with and without PVAT from control, diet-induced obese, calorie restricted and sustained weight loss rats. Changes in the PVAT environment were assessed using immunohistochemistry. PVAT from healthy animals elicited an anticontractile effect in response to norepinephrine. This was abolished in diet-induced obesity through a mechanism involving increased local tumor necrosis factor-α and reduced nitric oxide bioavailability within PVAT. Sustained weight loss led to improvement in PVAT function associated with restoration of adipocyte size, reduced tumor necrosis factor-α, and increased nitric oxide synthase function. This was associated with reversal of obesity-induced hypertension and normalization of plasma adipokine levels, including leptin and insulin. Conclusions—: We have shown that diet-induced weight loss reverses obesity-induced PVAT damage through a mechanism involving reduced inflammation and increased nitric oxide synthase activity within PVAT. These data reveal inflammation and nitric oxide synthase, particularly endothelial nitric oxide synthase, as potential targets for the treatment of PVAT dysfunction associated with obesity and metabolic syndrome. Abstract : Supplemental Digital Content is available in the text.